Prediction of Symptomatic Embolism in Infective Endocarditis - Hubert, Sandrine; Thuny, Franck; Resseguier, Noemie; Giorgi, Roch; Tribouilloy, Christophe; Le Dolley, Yvan; Casalta, Jean-Paul; Riberi, Alberto; Chevalier, Florent; Rusinaru, Dan; Malaquin, Dorothée; Remadi, Jean Paul; et al. (Journal of the American College of Cardiology, 2013)
The aim of this study was to develop and validate a simple calculator to quantify the embolic risk (ER) at admission of patients with infective endocarditis. Early valve surgery reduces the incidence of embolism in high-risk patients with endocarditis, but the quantification of ER remains challenging. From 1,022 consecutive patients presenting with definite diagnoses of infective endocarditis in a multicenter observational cohort study, 847 were randomized into derivation (n = 565) and validation (n = 282) samples. Clinical, microbiological, and echocardiographic data were collected at admission. The primary endpoint was symptomatic embolism that occurred during the 6-month period after the initiation of treatment. The prediction model was developed and validated accounting for competing risks. The 6-month incidence of embolism was similar in the development and validation samples (8.5% in the 2 samples). Six variables were associated with ER and were used to create the calculator: age, diabetes, atrial fibrillation, embolism before antibiotics, vegetation length, and Staphylococcus aureus infection. There was an excellent correlation between the predicted and observed ER in both the development and validation samples. The C-statistics for the development and validation samples were 0.72 and 0.65, respectively. Finally, a significantly higher cumulative incidence of embolic events was observed in patients with high predicted ER in both the development (p < 0.0001) and validation (p < 0.05) samples. The risk for embolism during infective endocarditis can be quantified at admission using a simple and accurate calculator. It might be useful for facilitating therapeutic decisions.